Nature-Based Learning Design to Strengthen the Indonesian Language Learning Program at Kursus Pengetahuan Dasar Indonesia (KPDI) Davao, Mindanao, Philippines - Yudhawasthi, Ciwuk Musiana; Dewi, Rezki Intan Permata (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
Indonesian Language for non-native speakers is generally taught through formal schools with comprehensive learning facilities and professional teachers. Indonesian language lessons for non-native speakers are not entirely intended for foreign citizens but are also needed by Indonesian citizens who have lived for generations outside Indonesia. As a result, they need to relearn Indonesian language and culture. Kursus Pengetahuan Dasar Indonesia (KPDI) Davao, Philippines is a program created by the Consulate General of the Republic of Indonesia in the Davao working area which aims to Indonesianize Indonesian descendants spread across the Davao region, Philippines. However, this program did not run optimally due to the lack of professional teachers and adequate learning facilities. Despite efforts by the Consulate General of the Republic of Indonesia in Davao to provide modules for teachers or instructors and implement monitoring and evaluation programs to ensure the learning is ongoing. This research aims to provide input on nature-based learning designs that can be implemented easily and efficiently by instructors to help improve students' vocabulary and communication skills at Kursus Pengetahuan Dasar Indonesia (KPDI) in Davao, Mindanao, Philippines. Using a qualitative approach, data collection was carried out through interviews, observation, and literature studies. The results of the research show the importance of improving modules, mentoring and providing direction to teachers to design learning methods with students-based learning approaches.